Including public health considerations in trade and investment agreements. (30th September 2020) - Thow, A; Garde, A; Mabhala, M; Smith, R; Kingston, P; Manning, P; Hunter, D; Winters, L A; Lincoln, P; Parish, R
Abstract: There is widespread recognition that trade and investment agreements (TIAs) can affect health services, access to medicines, NCD prevention (particularly related to tobacco, alcohol and unhealthy food) and health systems structures. In addition, these binding international economic agreements can constrain the policy space available for innovative, evidence-based health policymaking. Although TIAs can have positive outcomes for employment and economic growth, these benefits are only likely to accrue when governments are pro-active in implementing complementary policies to mitigate impacts on other sectors and to address potential inequalities arising. The aim of this panel session is to examine the ways in which TIAs can be designed to achieve economic goals while also protecting public health, and identify complementary policy measures that may be needed as well as strategies for strategic policy engagement. This panel will be hosted by the UK-PRP PETRA Network (Prevention of noncommunicable disease using trade agreements). The UK will be negotiating a range of new TIAs over the coming years, representing a window of opportunity for strategic engagement with policymakers regarding how public health can be protected and promoted within these agreements. There is an emerging global body of evidence regarding how consideration of health can be integrated into TIAs, both textually and through strategic engagement with policymakers before and during the negotiation phase. Experience to date indicates common global challenges and opportunities for health and trade, as well as significant potential for cross country learning regarding trade and health. The panel discussion will use the UK experience as a springboard to address these global issues.